Gestión productiva de los pequeños agricultores de ciclo corto y el desarrollo socioeconómico de las familias del Cantón Montalvo, provincia de los Ríos - Rivadeneira Avilez, Gabriela (2015)
The productive activity of small farmers engaged in cultivation of short cycle in any sector of the country, contributing to the socioeconomic development of the community and Ecuador, so this research developed in the canton Montalvo, is of utmost importance because will determine the family's economic and society montalvina contribution.